Effect of ion beam modifications on the surface and structural properties of β-FeSi2 thin films - Tatar, Beyhan; Kutlu, Kubilay; Ruergen, Mustafa (IOP PUBLISHING LTD, 2007)
We have investigated the effect of ion bombardment during and after deposition on the structure and surface properties of semiconducting beta-FeSi2 thin films grown on n-Si( 1 0 0) substrates at room temperature by unbalanced magnetron sputtering. The properties of beta-FeSi2 thin films were characterized with field emission gun scanning electron microscopy, atomic force microscopy, x-ray diffraction analysis and Raman spectroscopy. Ion bombardment of the films after deposition resulted in grain size refinement and decreased the crystallinity of the films. However, ion bombardment during deposition increased the crystallinity and grain size of the coatings. These modifications induced by ion bombardment are also expected to affect the photovoltaic performance.
Keywords: DEPOSITION; SILICON; SI(111); FESI2; TEMPERATURE; EPITAXY; GROWTH; FE; SI; Physics